Microstructure design for fast lifetime measurements of magnetic tunneling junctions - Parra, Andres Conca; Casper, Frederick; Paul, Johannes; Lehndorff, Ronald; Haupt, Christian; Jakob, Gerhard; Klaeui, Mathias; Hillebrands, Burkard (Sensors, 2019)
The estimation of the reliability of magnetic field sensors against failure is a critical point concerning their application for industrial purposes. Due to the physical stochastic nature of the failure events, this can only be done by means of a statistical approach which is extremely time consuming and prevents a continuous observation of the production. Here, we present a novel microstructure design for a parallel measurement of the lifetime characteristics of a sensor population. By making use of two alternative designs and the Weibull statistical distribution function, we are able to measure the lifetime characteristics of a CoFeB/MgO/CoFeB tunneling junction population. The main parameters governing the time evolution of the failure rate are estimated and discussed and the suitability of the microstructure for highly reliable sensor application is proven.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Failure; MGO; MTJ; Reliability; Sensor; Stress; TMR; Tunneling barrier; Weibull